Development of HIV-1 fusion inhibitors targeting gp41 - Lu, K. (2014)
The HIV-1 envelope protein glycoprotein 41 (gp41) is crucial in the HIV-1 infection process, therefore gp41 has emerged as an attractive target for drug design against AIDS. During the past few decades, tremendous efforts have been made on developing inhibitors that can prevent the HIV-1 entry process via suppressing functional gp41. In this review, the development of HIV-1 fusion inhibitors targeting gp41 including peptide inhibitors, small molecule inhibitors, vaccines and neutralized antibodies will be discussed.